2017
DOI: 10.1097/tp.0000000000001478
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Transplantation of Bone Marrow Mononuclear Cells Promotes Axonal Regeneration and Analgesia in a Model of Wallerian Degeneration

Abstract: These data demonstrate the efficiency of BMMC, systemically and noninvasively transplanted, in correcting morphological, functional and behavioral alterations resulting from peripheral nerve injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 62 publications
5
17
0
Order By: Relevance
“…Working with systemically transplanted bone marrow mononuclear cells (BMMC), a heterogeneous fraction including mesenchymal stem cells (MSC), our group demonstrated beneficial effects on sciatic nerve regeneration, together with prevention of hyperalgesia in a Wallerian degeneration (WD) model. [4,5] MSC are adult stem cells, originally described only in bone marrow, which possess self-renewal and multi-lineage differentiation potential. They were popularized in 1991 by Arnold Caplan, who reported their ability to give rise to bone and cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…Working with systemically transplanted bone marrow mononuclear cells (BMMC), a heterogeneous fraction including mesenchymal stem cells (MSC), our group demonstrated beneficial effects on sciatic nerve regeneration, together with prevention of hyperalgesia in a Wallerian degeneration (WD) model. [4,5] MSC are adult stem cells, originally described only in bone marrow, which possess self-renewal and multi-lineage differentiation potential. They were popularized in 1991 by Arnold Caplan, who reported their ability to give rise to bone and cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…An additional major pitfall is the need of lengthy and strict aseptic processes involving sample acquisition, culturing, expansion, and maintenance to obtain enough cells to be administered. 1,59 Therefore, strategies promoting endogenous MSCs mobilization seem more desirable from a therapeutic stand point. 39 Sponsorships or competing interests that may be relevant to content are disclosed at the end of this article.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al (2016) found that VEGF-expressing neural stem cells could enhance cell viability under hypoxic conditions and facilitate remyelination of injured sciatic nerves. Transplanted bone marrow mononuclear cells could migrate to the damaged site and promote neovascularization and tissue repair, electromyogram compound muscle action potential (CMPA) verified the presence of regenerated axons (Usach et al, 2017).…”
Section: Neuroprotection and Remyelinationmentioning
confidence: 95%
“…Takamura et al (2020) found that intrathecal injection of BMMCs attenuated NP in a mice model of spinal nerve transection (SNT). Animal experiments by Klass et al (2007) and Usach et al (2017) exhibited that intravenous injection of BMMCs could relieve NP caused by sciatic nerve crush or constriction. In addition to suppressing microglial migration and inflammation associated with nerve injury, a range of angiogenic ligands (basic fibroblast growth factor, angiopoietin-1, VEGF) and cytokines (IL-1b, TNF-a) were secreted by BMMCs to promote local neovascularization and tissue repair (Naruse et al, 2011).…”
Section: Bone Marrow Mononuclear Cellsmentioning
confidence: 99%
See 1 more Smart Citation